KOMITMEN ORGANISASI - Bambang Supriyanto (Universitas Negeri Jakarta, 2012)
The objective of the research is to study the effect of organizational culture, organizational justice, and job satisfaction to organizational commitment in the National Education Department in around the Government of Gorontalo’s Province. Sample study involving 310 civil servants. The research used survey method and structural equation modelling’s technique.The results are: (1) organizational culture directly positive affects organizational commitment, (2) organizational justice directly positive affects organizational commitment, (3) job satisfaction had a directly positive impact on organizational commitment, (4) organizational culture directly positive effects job satisfaction, (5) organizational justice directly influence job satisfaction, (6) organizational culture directly positive effects organizational justice. Based on this research, the factors of organizational culture, organizational justice, job satisfaction and organizational commitment should be take into consideration by leaders at the National Education Department in around the Local Government in Gorontalo to raise the organizational commitment.